1991
DOI: 10.1172/jci115456
|View full text |Cite
|
Sign up to set email alerts
|

Antimalarial effects of peptide inhibitors of a Plasmodium falciparum cysteine proteinase.

Abstract: We previously identified a Plasmodiumfalciparum trophozoite cysteine proteinase (TCP) and hypothesized that it is required for the degradation of host hemoglobin by intraerythrocytic malaria parasites. To test this hypothesis and to evaluate TCP as a chemotherapeutic target, we examined the antimalarial effects of a panel of peptide fluoromethyl ketone proteinase inhibitors. For each inhibitor, effectiveness at inhibiting the activity of TCP correlated with effectiveness at both blocking hemoglobin degradation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
127
0
1

Year Published

1994
1994
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 175 publications
(130 citation statements)
references
References 24 publications
2
127
0
1
Order By: Relevance
“…Similar discrepancies, attributed to inefficient uptake of compounds into the parasite, have been reported with inhibitors of the P. falciparum cysteine proteases (55) or dihydroorotate dehydrogenase (56). Limited cell permeability could equally be a cause for the discrepancy between whole-cell and enzyme inhibition values observed with triclosan and its analogs, particularly in view of the requirement for apicoplast inhibitors to traverse four membranes surrounding this organelle (4,24) in addition to the host cell and parasite membranes.…”
Section: Journal Of Biological Chemistry 25439mentioning
confidence: 60%
“…Similar discrepancies, attributed to inefficient uptake of compounds into the parasite, have been reported with inhibitors of the P. falciparum cysteine proteases (55) or dihydroorotate dehydrogenase (56). Limited cell permeability could equally be a cause for the discrepancy between whole-cell and enzyme inhibition values observed with triclosan and its analogs, particularly in view of the requirement for apicoplast inhibitors to traverse four membranes surrounding this organelle (4,24) in addition to the host cell and parasite membranes.…”
Section: Journal Of Biological Chemistry 25439mentioning
confidence: 60%
“…Considering the role of this enzyme in a unique and essential metabolic pathway, it warrants further investigation. FLN may be a worthy drug target as it has been shown that inhibition of hemoglobin catabolism is lethal to parasites [14,15]. In this study, we show that FLN, unlike other food vacuole proteases, does not have a propiece.…”
mentioning
confidence: 56%
“…Disruption of the FP2 gene led to the accumulation of undegraded hemoglobin in trophozoites, confirming a critical role for this enzyme in hemoglobin hydrolysis (10). Inhibition of FP2 and related proteases led to a block in parasite development (11,12) and cured mice with murine malaria (13,14), and efforts to develop falcipain inhibitors as new antimalarial agents are underway. These efforts will be facilitated by a detailed understanding of the biochemical properties of FP2.…”
mentioning
confidence: 92%